WATERMARKING CITRA DIGITAL BERWARNA MENGGUNAKAN STATIONARY WAVELET TRANSFORM (SWT) - Umar, Fitriani; Darwis, Herdianti (Univeristas Muslim Indonesia, 2019)
Digital Image watermarking is widely used and studied for ownership identification, data protection, and authentication. A good watermarking scheme should achieve the watermarking requirements such as imperceptibility, robustness and capacity. This research aims to make robust and imperceptible watermarking by using Stationary Wavelet Transform. The test is done on two levels of transformation and attacked by Salt and Pepper, Speckle, Gaussian Noise, Blur, Compression and Rotation. The results show that method used in this research gives good impercebtility with PSNR value larger than 70 dB on level 1 and larger than 40 dB on level 1. The Robustness test also shows a good result where Normalized Correction value larger 0.9466 on level 1 and larger than 0.9714 on level 2. This also shows that for imperceptibilty, level 1 of transformation gives higher results than in level 2 of transformation, while for robustness, level 2 achieves better value than level 1.